The Clock Counts – Length Effects in English Dyslexic Readers - Provazza, S.; Giofrè, D.; Adams, A.-M.; Roberts, D. J. (Frontiers in Psychology, 2019)
In reading, length effects are defined as an increment in the time taken to read as a function of word length and may indicate whether reading is proceeding in an efficient whole word fashion or by serial letter processing. Length effects are generally considered to be a pathognomonic symptom of developmental dyslexia and predominantly have been investigated in transparent orthographies where reading impairment is characterized as slow and effortful. In the present study a sample of 18 adult participants with developmental dyslexia were compared to a matched sample of typical developing readers to investigate whether the length effect is a critical aspect of developmental dyslexia in an opaque orthography, English. We expected that the developmental dyslexia group would present with marked length effects, in both words and nonwords, compared to typical developing readers. The presence of length effects in the developmental dyslexia group confirmed our prediction. These effects were particularly strong in low frequency words and in nonwords, as observed in reading speed. These preliminary findings may have important theoretical implications for current understanding of developmental dyslexia.